Rescue Therapy for Impacted Large Chicken Bone in the Esophagus: Argon Plasma Coagulation–Assisted Endoscopic Removal – A Case Report - Akpinar, Muhammet Yener; Sahin, Hasan; Bakir, Tolga; Gulsen, Mustafa (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Akpinar MY, Sahin H, Bakir T, Gulsen M. Rescue therapy for impacted large chicken bone in the esophagus: Argon plasma coagulation–assisted endoscopic removal – a case report. Turk J Gastroenterol. Published online November 3, 2025. doi:10.5152/tjg.2025.25481.